Evaluation of a QTL Mapping Population Composed of Hard Red Spring and Winter Wheat Alleles Using Various Marker Platforms. Issue 2 (1st March 2018) - Cook, Jason P.; Heo, H. ‐Y.; Varella, A. C.; Lanning, S. P.; Blake, N. K.; Sherman, J. D.; Martin, J. M.; See, D.; Chao, S.; Talbert, L. E.
Abstract : Hard red spring and winter wheat ( Triticum aestivum L.) differ due to the need for vernalization to induce flowering in winter wheat, adaptation to different environments, and the requirement for higher grain protein content for end‐use quality in spring wheat. Genetic studies on spring × winter wheat crosses to identify beneficial alleles are difficult due to segregation of vernalization ( Vrn ) genes. For this experiment, 'Yellowstone', a widely grown winter wheat cultivar, was converted to the spring habit through marker‐assisted backcrossing of Vrn‐A1 and is now referred to as 'S‐Yellowstone'. S‐Yellowstone was crossed to the spring wheat cultivar 'Choteau' to produce a population of 95 spring habit recombinant inbred lines (RILs). The RILs and parents were evaluated in field trials for 2 yr where S‐Yellowstone had higher grain yield and lower grain protein than Choteau. A quantitative trait locus (QTL) on chromosome 4A had pleiotropic effects on several traits. The S‐Yellowstone allele at this locus resulted in more seeds per head, accounting for 59.5% of the variation across all environments. The QTL was designated QSnh.mst‐4A . However, the S‐Yellowstone QSnh.mst‐4A allele also resulted in lower grain protein across all environments. Results suggest that the favorable QSnh.mst‐4A allele for seed number per head identified in the winter wheat parent might be useful for increasing yield in spring wheat, but consequences of the negative pleiotropic effects on grain protein content might be significant.